Infant mortality and epidemic diseases. Wartime Finnmark in a comparative perspective - Mølmann, Nina Planting; Jacobsen, Bjarne K.; Elstad, Ingunn (Nordlit, 2015)
The effects of war on the health of the population have never been systematically studied. The article explores the impact of war on the general health condition of Finnmark’s population during the war years. The indicators chosen are infant mortality and the epidemic diseases diphtheria, scabies and acute gastroenteritis. The development of the indicators in Finnmark is compared with the averages in Norway and Finnish Lapland. The findings deserve attention. The article discusses the statistical indicators and findings in a social and historical context with a range of sources. The article is a broad as well as penetrating analysis of the war’s impact on the health of the civilian population of Finnmark and on their everyday living and survival.